Behavioral Barriers to Energy Efficiency and Policy Interventions: A Survey of the Literature - Bensouda, Mehdi; Benali, Mimoun (International Journal of Energy Economics and Policy, 2022)
The increasing energy demand implying the depletion of fossil fuels and a worsening of poverty, and the alarming level of pollution leading to an unprecedented climate urgency, call for a rapid reduction of energy consumption. Despite the global recognition of the compelling benefits of energy efficiency, there is still a gap between the theoretical potential and the current level of energy efficiency. Agents’ irrational hesitation to invest in energy efficiency explains a significant proportion of the energy efficiency gap. Behavioral barriers have caused policymakers to question the relevance of traditional information-based instruments. To address behavioral obstacles, a reconsideration of traditional policies appears to be necessary. We examine the key barriers related to agents’ behavior and how they reinforce each other. Then we suggest that policies should consider nudging strategies, which offer valuable insights regarding the human decision-making, and which represent a pivotal way to close the energy efficiency gap.